Extraocular Myoplasty: Surgical Remedy For Intraocular Implant Exposure - Singh, Anupam; Vathulya, M; Agrawal, Ajai; Verma, Rupal; Mittal, S. K.; Kumar, Barun; Aggarwal, Kirti (Nepalese Journal of Ophthalmology, 2020)
Background: Evisceration and nucleation are commonly performed ophthalmic surgeries for painful blind eye, disfiguring blind eye, endophthalmitis etc. After both these surgeries it is important to replace the lost volume in the orbit with implant. Implant is associated with many complications such as major discharge, exposure with discharge and implant exposure. The main surgical management of implant exposures basically primary revision or patch grafting with or without removal of the implant. Case: A 60 years old man presented to ophthalmic OPD with complaint of foreign body sensation and irritation in left eye. There was history of evisceration with silicon ball implant in left eye done one month back for painful blind eye at another hospital. On ophthalmic examination, there was a 3 × 4 mm of implant exposure most probably dueto tight closure. As per records the size of implant was 22mm. The patient was planned for extra-ocular myoplasty with buccal mucosal graft under general anesthesia. Observation: After sterile prepping and draping, 360˚ degrees peritomy was performed and care was taken to dissect between tenons and orbital implant. Medialand lateral recti were isolated and dissected upto 10-12mm from insertion site. Both the recti were secured with 6-0 vicryl suture and were detached from their respective insertions, advanced and approximated over the site of implant exposure. Thus the exposed implant was covered with a vascularized base which was reinforced with amucosal graft harvested from the buccal mucosa and secured with absorbable sutures. After 1 year of follow up patient was asymptomatic. Conclusion: Extraocular myoplasty with buccal mucosal graft is a good surgical remedy for orbital implant exposure implant.